Does cyclosporin A adversely affect Pneumocystis carinii infection?. Issue 755 (September 1988) - McGonigle, R. J.; Beaman, M.; Stone, J.; Young, J.; Michael, J.; Adu, D.
Abstract : Fourteen immunosuppressed patients with Pneumocystis carinii infection presented in two clusters that were separated by 2 years. The diagnosis in all cases was made early by alveolar lavage with cytology. The first group of seven patients was immunosuppressed with cyclophosphamide or azathioprine and prednisolone. All recovered with high dose co-trimoxazole. The second group of seven patients was on prednisolone and cyclosporin A. Despite identical treatment three patients died and a further two who survived lost their grafts from rejection. Our data suggest that cyclosporin A adversely affects the prognosis from Pneumocystis carinii infection and raises the question of prophylactic co-trimoxazole in these patients. The clustering of Pneumocystis carinii infection suggests the possibility of nosocomial transmission although in this study we were unable to implicate person-to-person spread of infection.